Technology of plant factory for vegetable crop speed breeding - He, Rui; Ju, Jun; Liu, Kaizhe; Song, Jiali; Zhang, Shuchang; Zhang, Minggui; Hu, Youzhi; Liu, Xiaojuan; Li, Yamin; Liu, Houcheng (Frontiers in Plant Science, 2024)
Sustaining crop production and food security are threatened by a burgeoning world population and adverse environmental conditions. Traditional breeding methods for vegetable crops are time-consuming, laborious, and untargeted, often taking several years to develop new and improved varieties. The bottlenecks of long breeding cycle need to be overcome. Speed breeding (SB) approach is broadly employed in crop breeding, which greatly shortens breeding cycles and facilities to obtain new, better-adapted crop varieties as quickly as possible. Potential opportunities are offered by SB in plant factory, where optimal photoperiod, light quality, light intensity, temperature, CO2 concentration and nutrients, are precisely manipulated to enhance the growth of horticultural vegetable crops, holding promise to surmount the long-standing bottleneck of lengthy crop breeding cycles.Additionally, integrated with other breeding technologies, such as genome editing, genomic selection and high throughput genotyping, SB in plant factory has emerged as smart and promising platforms to hasten generation turnover and enhance the efficiency of breeding in vegetable crops. This review considers the pivotal opportunities and challenges of SB in plant factory, aiming to accelerate plant generation turnover and improve vegetable crops with precision and efficiency.